AODV-HE routing algorithm based on minimum hop and energy of node - Xiang YU; Zhi PENG; Shiyan WANG; Li LIU (Dianxin kexue)
AODV routing protocol takes the minimum hop as the only basis in route selection，causing the uneven allocation of resources and reduction in network lifetime.A routing algorithm based on minimum hops and energy of node（AODV-HE）was proposed.By integrating both minimum hop and residual energy of each node，the algorithm optimized the routing mechanism and presented a selection weight of reverse routing，based on which the best route was chosen.Simulation results show that the algorithm can effectively increase packet delivery ratio and reduce the end-end delay，and it can also improve the allocation of network resources and extend network lifetime.